Simultaneous detection of sulfoxaflor and its metabolites, X11719474 and X11721061, in lettuce using a modified QuEChERS extraction method and liquid chromatography–tandem mass spectrometry. (19th December 2016) - Kim, Sung‐Woo; Rahman, Md. Musfiqur; Abd El‐Aty, A. M.; Kabir, Md. Humayun; Na, Tae Woong; Choi, Jeong‐Heui; Shin, Ho‐Chul; Shim, Jae‐Han
Abstract: An analytical method has been developed to quantify the residual levels of sulfoxaflor and its metabolites (X11719474 and X11721061) in/on cultivated lettuce grown under greenhouse conditions. Samples were extracted and purified using a quick, easy, cheap, effective, rugged, and safe 'QuEChERS' method (original version) following systematic method optimization and were analyzed by liquid chromatography–tandem mass spectrometry (LC–MS/MS). Good linearity with coefficient of determination ≥0.9930 was obtained and the limits of detection (LOD) and quantification (LOQ) were in the ranges of 0.003–0.006 and 0.01–0.02 mg/kg, respectively. The recovery rates of both the parent compound and its metabolites (fortified at 10 and 50× the LOQ) estimated from six replicates ranged between 81.9 and 115.5% with a relative standard deviation <12%. The validated method was applied to field‐incurred samples (collected over 7 days) sprayed once or twice with a water‐dispersible granule formulation. Notably, a substantial reduction in rate was observed after 3 days and the half‐life was short, only 1.5 days. The developed method is simple and versatile and can be used for various leafy vegetables.